The Impact of the Corona Pandemic on the Revenues and Expenditures of the Jordanian General Government and the Gross domestic Product - Jreisat , Sami Sanyal; Radaideh, Morad Khaled; Al-Hyari, Hadeel Sa'ad Muhammed; Al-Muhtadi, Akram Mohammad Irfan (Journal of Ecohumanism, 2024)
The research aimed to know The impact of the Corona pandemic on the revenues and expenditures of the Jordanian general government and the gross domestic product And reached the following results: The Corona Covid-19 pandemic is greater than being limited to a health crisis, it is a humanitarian disaster that led to changes and transformations that attacked the heart of societies and their economies, so it was imperative for countries to work on the continuity of economic activity and the preservation of the wheel of production in the country while limiting the spread of the disease. It led to a complete and total halt to any economic activity, which caused the cancellation of many capital expenditures scheduled in the context of strict measures, as the restrictions imposed on travel and trade resulted in a decrease in revenues and an increase in expenditures, and the Corona pandemic caused an increase in the deficit rate in the state's general budget, as a result of the large expenses incurred by the state, with a clear decrease in annual revenues, but the state was able in the years following the pandemic to reduce the deficit rate in the budget and cancel many capital expenditures and freeze the performance of some economic activities, which is considered a severe blow to the domestic product, considering that revenues and expenditures enable the state to play its role effectively, as the decrease in revenues and the increase in expenditures call for a review of the structure of government institutions and the duties assigned to them The services it provides, which calls for a mix of its services to ensure mitigation of the pandemic and any crisis that the country may be exposed to, which confirms the validity of the first hypothesis and in light of such crises, and practicing that pivotal role that links the actors in the economic sectors, which allows them to be stronger than before, which confirms the validity of the second hypothesis. They recommended the following: Establishing permanent centers for crisis and risk management at the state level and at the level of the various economic sectors, and activating coordination between them to deal with various crises and risks, and developing training programs for workers on how to deal with crises and how to deal with their effects, and appointing experts and specialists to monitor, analyze and prepare reports on the various crises that the various sectors are going through and building a comprehensive database to predict crises before they occur. 10- Strengthening relations between the various governmental, civil and economic sectors with the media institutions due to their importance in spreading awareness and participating in conferences and interviews that help spread knowledge, and the need to benefit from the experiences of other countries in how to overcome crises.